Gaya Iltifat dalam Al-Qur'an - Muhsin Ahmad (Diwan : Jurnal Bahasa dan Sastra Arab, 2019)
إن ظهور الاتهامات بأن القران يحتوي على أخطاء نحوية هو أمر خاطئ ، لأنه إقتصر دراسته القران من ناحية لغوية على حين أهمل النظر إلي مكانة القرآن كأعظم كتاب لأدب العربي. إن المبدأ الأساسى فى الأدب، الابتعاد عن الاتفاقية او نقض العادة لأن هذا هو الذى يثىر الإنتياه.  من خلال نهج أدبي مع الأساليب النوعية, يوجد في القرآن عديد من الكلمات والعبارات التي لا  تتفق مع  القواعد  التقليدية . لكن لا يمكن   اعتباره  خطأ تلقائيًا.  ويعرف  هذا  الانحراف  باسم  إزالة  الصفات  المألوفة   (defamiliarization)  أو إلغاء الأتمتة (de-autoamation)  المسمى في الأدب العربي بالإلتفات. هذا الأسلوب المثير للإعجاب هو معجزة قادرة على أسر وإخضاع الشعراء العرب عند نزول القرآن ، لذا فهم يريدون أن يعترفوا بأن محمدا رسول الله.الكلمات المفتاحية : القران؛ معجزة؛ الإلتفات؛ الانحراف AbstractThe accusation that the Qur'an contains many grammatical errors is wrong because it only examines the Qur'an from the linguistic side without regard to the position of the Qur'an as the greatest Arabic literary book. The basic nature of literature is to deviate from the ordinary, because that's where the attraction lies. Through a literary approach with qualitative methods, in the Koran, several words and phrases that are not in accordance with conventional rules are found, but not necessarily be considered a mistake. This deviation is known as defamiliarization or de-automation which in Arabic literature is called iltifat. This impressive style is a miracle that is able to captivate and subdue the Arabic poets when the Qur'an was revealed, so they want to acknowledge that Muhammad is the messenger of God.